2015
DOI: 10.1093/eurheartj/ehv443
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dual antiplatelet therapy for secondary prevention of cardiovascular events in the subgroup of patients with previous myocardial infarction: a collaborative meta-analysis of randomized trials

Abstract: Compared with aspirin alone, DAPT beyond 1 year among stabilized high-risk patients with prior MI decreases ischaemic events, including significant reductions in the individual endpoints of cardiovascular death, recurrent MI, and stroke. Dual antiplatelet therapy beyond 1 year increases major bleeding, but not fatal bleeding or non-cardiovascular death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
2
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 246 publications
(198 citation statements)
references
References 55 publications
4
173
2
19
Order By: Relevance
“…Patients presenting with acute coronary events may have more persistent platelet activation and thus have more favorable ischemic-bleeding balance with prolonged DAPT [24]. This assumption is supported by a recent meta-analysis by Udell et al showing reduction in major adverse cardiovascular events (including cardiovascular mortality) with extended DAPT in patients with history of MI [25]. Similarly, there was no significant reduction in MACE in the L-APT arm of DAPT trial among patients who received everolimus eluting stents [9].…”
Section: Resultsmentioning
confidence: 88%
“…Patients presenting with acute coronary events may have more persistent platelet activation and thus have more favorable ischemic-bleeding balance with prolonged DAPT [24]. This assumption is supported by a recent meta-analysis by Udell et al showing reduction in major adverse cardiovascular events (including cardiovascular mortality) with extended DAPT in patients with history of MI [25]. Similarly, there was no significant reduction in MACE in the L-APT arm of DAPT trial among patients who received everolimus eluting stents [9].…”
Section: Resultsmentioning
confidence: 88%
“…The SMART‐REACH model, incorporated in an online calculator (eg, Supplemental Calculator and http://www.U-Prevent.com), may support clinical decision making on (novel) therapeutic options by estimating an individual's anticipated treatment benefit in terms of life expectancy without recurrent cardiovascular events. This may particularly be of value for novel effective but costly agents such as PCSK9 inhibitors, potent antithrombotics, and anti‐inflammatory agents 23, 35, 36, 37. Ideally, such treatment effect estimations are validated on the basis of the original trial data of such novel therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recent studies have shown further reduction in ischemic events by dual antiplatelet therapy (DAPT) beyond 1 year after an ACS and PCI. [4][5][6] Patients with ACS are, however, heterogeneous regarding the risks for both ischemic and bleeding events. The most recent European Society of Cardiology non-ST-elevation ACS guidelines state that more-intense and prolonged P2Y 12 inhibition may be considered, taking into account the individual ischemic and bleeding risks.…”
mentioning
confidence: 99%